Импульсный СВЧ-компрессор с передачей энергии между видами колебаний; Известия вузов. Физика; Т. 54, № 11(2) - Августинович В. А. Владимир Андреевич; Артеменко С. Н. Сергей Николаевич; Игумнов В. С. Владислав Сергеевич; Новиков С. А. Сергей Автономович (2011, 2011)
Заглавие с экрана